Shaping Professional Skills in Intercultural Dialogues - A Case Study of "Polish Language Across Borders" Project - Jarosław Krajka; Małgorzata Latoch-Zielińska (Maria Curie-Skłodowska University, Lublin, Poland, 2024)
Introduction: The contemporary world demands that employees in different work contexts do not only possessthe necessary professional knowledge and skills but also exhibit a necessary level of intercultural communicative competence that enables them to interact successfully with multilingual and multicultural clients, peers and students. While university programmes do have necessary arrangements for practicum, students often perceive this professional practice as insufficient in the development of social and intercultural skills. Research Aim: The purpose of the present study was to investigate whether students of different study programmes would find participation in the intercultural "Polish language across borders" project as a viable alternative to traditionally serving the practicum. Another aim of the research was to see how voluntary participation in an out-of-study project would contribute to the development of professional, social and communicative competencies. Method: The study followed the qualitative methodology, with the small-scale interview as a data collection procedure. The data were gathered from student coordinators of project participantsthrough an online interview. Results: As was evidenced by the data on the viability of alternative forms of serving practicum collected from student coordinators, encouraging students to volunteer in intercultural projects directed at foreign audiences leads to an increase in professional and intercultural competenciesas well as results in a high level of satisfaction and motivation upon the project's completion. The participants stressed the positive effect of participation in the project on their readiness for the job market as well as noticed increased openness to and understanding of representatives of other cultures. Conclusions: Since traditional practicum often triggers feelings of inadequacy and insufficient authenticity among students, it is worthwhile organising non-formal education projects in the form of intercultural exchanges which would enable the acquisition of intercultural, professional and communicative skills in authenticinteractions with partners from abroad.